MODERASI DALAM MEMAKNAI HAK-HAK ANAK - Nurjanah, Siti (Moderatio: Jurnal Moderasi Beragama, 2022)
This paper discusses the concept of moderation in addressing children's rights in terms of family, environment and society. This paper uses a descriptive qualitative research method that is literary in nature. The result of this paper is to emphasize that there arefour aspects of religious moderation that need to be the rights of children in achieving tolerant religious qualities, namely planting national commitment, strengthening tolerance, anti-violence, and introducing and preserving local culture. Strengthening religiousmoderation is a right to be taught to children from an early age in the family and community so that children are able to have moderate traits and prevent radicalismin the future.